KRITIK TERHADAP PERPU DI MASA PANDEMI: PEMBATASAN HAK TANPA KEDARURATAN - Victor Imanuel W. Nalle (Faculty of Law, Universitas Gadjah Mada, 2021)
Abstract After establishing a public health emergency with Presidential Decree No.11 of 2020, President Joko Widodo issued a Government Regulation in Lieu of Law No. 1 of 2020 (Perppu No.1 of 2020). Perppu No. 1 of 2020 was like becoming emergency legislation by suspending the right to examine government administration decisions. This article criticizes the arguments that place Perppu No. 1 of 2020 as emergency legislation which then allows the violation of the rule of law or suspends the rights of citizens. This article uses the comparative law method by examining the concept of fast-track legislation in the UK and Ecuador and comparing it to the concept of emergency legislation as a basis for criticism of the Perppu no. 1 of 2020. This criticism is carried out from the perspective of both emergency legislation and fast-track legislation. This article shows that the Perppu No. 1 of 2020 should be classified as limited as fast track legislation that cannot suspending citizens’ rights. Intisari Setelah menetapkan darurat kesehatan masyarakat dengan Keputusan Presiden Nomor 11 Tahun 2020, Presiden Joko Widodo menetapkan Peraturan Pemerintah Pengganti Undang-Undang No. 1 Tahun 2020 (Perppu No. 1 Tahun 2020). Perppu No. 1 Tahun 2020 seolah-olah menjadi legislasi darurat dengan menangguhkan hak untuk menguji keputusan administrasi pemerintahan. Artikel ini mengkritik argumen yang menempatkan Perppu No. 1 Tahun 2020 sebagai legislasi darurat yang kemudian memungkinkan penyimpangan aturan hukum atau menangguhkan hak warga negara. Artikel ini menggunakan metode perbandingan hukum dengan mengkaji konsep legislasi jalur cepat di Inggris dan Ekuador dan membandingkannya dengan konsep legislasi darurat sebagai dasar kritik bagi konsep Perppu No. 1 Tahun 2020. Artikel ini menunjukkan bahwa Perppu No. 1 Tahun 2020 seharusnya diklasifikasikan sebatas sebagai legislasi jalur cepat yang tidak dapat menangguhkan hak warga negara.